2015
DOI: 10.1177/0021998314567698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zirconia and aluminium titanate on the mechanical properties of transformation-induced plasticity-matrix composite materials

Abstract: Metal-matrix composite materials composed of an austenitic stainless steel with different ceramic particle reinforcements were investigated in this study. The test specimens were prepared via a powder metallurgical processing route with extrusion at room temperature. As reinforcement phase, either magnesia partially stabilized zirconia or aluminium titanate with a volume content of 5% or 10% was used. The mechanical properties were determined by quasi-static compressive and tensile loading tests at ambient tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The high diffusivity and reactivity promote the formation of merging solid solutions with lenticular morphology in the system Ti–Mn–Al–O with minor fractions of Fe, Cr, and Si and of isolated rod‐like constituents based on the clearly different composition with weight fractions of 30% Al 2 O 3 , 10% MnO, and 60% TiO 2 . The microstructure of the composite materials with concurrent additions of TiO 2 and Al 2 O 3 largely complied with the observations of composite materials with additions of presynthesized aluminum titanate . Locations with higher concentrations of Si in the interstices between the coarser grained steel and the ceramic particles were assumed to origin from the polishing medium (SiO 2 ).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The high diffusivity and reactivity promote the formation of merging solid solutions with lenticular morphology in the system Ti–Mn–Al–O with minor fractions of Fe, Cr, and Si and of isolated rod‐like constituents based on the clearly different composition with weight fractions of 30% Al 2 O 3 , 10% MnO, and 60% TiO 2 . The microstructure of the composite materials with concurrent additions of TiO 2 and Al 2 O 3 largely complied with the observations of composite materials with additions of presynthesized aluminum titanate . Locations with higher concentrations of Si in the interstices between the coarser grained steel and the ceramic particles were assumed to origin from the polishing medium (SiO 2 ).…”
Section: Resultssupporting
confidence: 65%
“…The rest was α'‐martensite and δ‐ferrite, which cannot be reliably distinguished due to their common bcc crystal structure. The phase composition of similar steel specimens usually alters during the thermal treatment of such powder metallurgically manufactured specimens as a result of the retransformation of martensite into austenite and/or intensive diffusional interactions between the metal and the ceramic component during sintering . The ferromagnetic fraction (martensite and ferrite) of the pure steel material was roughly 29% according to MSAT measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the water atomized steel powders have high oxygen content due to the thick oxide layer formed on the particle surface during production [16,17]. According to Y. Hedberg et al [18] the surface of water atomized steel particles are strongly enriched with oxidized Si (silicates).…”
Section: Fig 3 Sem Micrographs Of Plain 316l Compacts Sinteredmentioning
confidence: 99%
“…In particular, composites based on high-energy-absorbing transformation-induced plasticity (TRIP)/twinning-induced plasticity steels and transformable zirconia (ZrO 2 ) particles show great potential [20][21][22][23]. For instance, reinforcement with MgO-partially stabilized zirconia (Mg-PSZ) particles can increase the strength as well as the wear properties of these composites, owing to the ability of Mg-PSZ to undergo a stress-induced transformation from the tetragonal phase to the monoclinic phase [24][25][26]. Furthermore, the use of metastable austenitic steel as the matrix ensures a deformation-induced increase in both the strength and the ductility, owing to the TRIP effect [27,28].The aim of this study was to experimentally determine the forming conditions for the production of axially formed graded components from a particle-reinforced metal matrix composite using powder forging.…”
mentioning
confidence: 99%